Genetic diversity of Streptococcus suis isolated from pigs and humans in Chiang Mai and Lamphun province, Thailand - Korawan Wongsawan (2018)
Streptococcus suis is recognized worldwide as an important swine pathogen, which occasionally infects humans and causes fatal illness. Seventy-three isolates of S. suis from patients and healthy pigs in Thailand were characterized by serotyping, three putative virulence genes (mrp, epf, and sly) and pulsed-field gel electrophoresis (PFGE). Of the 73 isolates, 63 human and 6 pig isolates were serotype 2, and 2 human isolates were serotype 1, and the remaining 2 human isolates were serotype 1/2. The 3 genes (mrp, epf, and sly) were detected in the 73 isolates by polymerase chain reaction (PCR) and 7 different genotypes were obtained. Interestingly, 2 genotypes from the healthy pig isolates corresponded to genotypes of human isolates (mrp+epf-sly-and mrp-epf-sly+). To characterize more discriminatorily, the 73 isolates were then analyzed by PFGE, and they were divided into 36 PFGE patterns (12 pulsotypes and 24 single patterns). These results indicated a great genetic diversity among S. suis isolates from humans and pigs. However, one pulsotype contained 8 isolates from humans and 4 isolates from pigs belong to the same pulsotype, suggesting a transmission of S. suis from pigs to humans. © 2005 Elsevier B.V. All rights reserved.